Mecanismos morfofisiológicos de tolerância de Conyza canadensis ao glyphosate - Freitas, Aline Katiane Silva (2021)
Weed tolerance to herbicides is a problem that progressively affects crop yields, directly interfering with food production. The development of physiological and / or biochemical and genetic tolerance mechanisms can become the first step towards selection pressure and, consequently, the emergence of resistance. Therefore, this study aimed to verify the tolerance mechanism of Conyza canadensis (buva) to the herbicide glyphosate. The experiment was carried out in a greenhouse in a randomized block design, in a 3x4x3 factorial scheme, whose treatments were composed by the combination of three doses of the herbicide glyphosate [0, 1,080 and 2,160 g. e.a.ha-1 ] in four times of application [20, 30, 40 and 50 days after emergence (DAE) of the herb plants] and three times of evaluation after each application [24, 48 and 72 hours] with three repetitions. The intracellular concentrations of glyphosate, aminomethylphosphonic acid (AMPA), shikimic acid, quinic acid, specific mass, thickness and chemical composition of epicuticular wax were evaluated. The highest intracellular concentrations of glyphosate (146.7 mg.kg1 ) and AMPA (3.62 mg.kg-1 ) were verified with the application of 2,160 g and ha-1 at 20 DAE of the grape plants, while, application at 50 DAE reduced AMPA concentrations to zero. Consequently, the highest degradation rate (63.7%) of glyphosate to AMPA was found after 72 hours of application at 20 DAE. On the other hand, applications at 50 DAE reduced glyphosate degradation to AMPA to zero. The highest concentrations of intracellular shikimic acid were verified with the application of glyphosate at 30 DAE with values of 42.5, 96.9 and 131.8 µg.g-1 at 24, 48 and 72 hours respectively. The highest concentrations of quinic acid were verified with the application of glyphosate at 30 and 40 DAE, whose values after 24, 48 and 72 hours were 17.0 and 19.7 µg.g-1 , 23.7 and 26.1 µg.g-1 and 28.7 and 30.1 µg.g-1 respectively. There was a significant increase (38%) in the specific mass of epicuticular waxes from 20 to 50 DAE, with values going from 82.1 µg.cm-2 to 113.3 µg.cm-2 . The advancement of the development stages of Conyza canadensis plants also resulted in changes in the chemical composition of epicuticular waxes, characterized mainly by the increase in the concentrations of long-chain fatty acids (> 34 carbons), going from 4.2% to 17.2 % from 20 to 50 DAE. The cuticle thickness also increased significantly with values of 6.3 μm, 8.0 μm, 11.4 μm and 12.1 μm in thickness at 20, 30, 40 and 50 DAE respectively. The results obtained show that the control of Conyza canadensis must be carried out up to 30 DAE of the plants, and that the main tolerance mechanism that operates in this species is characterized by quantitative and qualitative changes in epicuticular waxes.